Comparison between two self-guided tinnitus pitch matching methods - Santacruz, Jose L.; de Kleine, Emile; van Dijk, Pim (Frontiers in Aging Neuroscience, 2023)
Introduction Tinnitus pitch matching is a procedure by which the frequency of an external sound is manipulated in such a way that its pitch matches the one of the tinnitus. The correct measure of the tinnitus pitch plays an important role in the effectiveness of any sound-based therapies. To date, this assessment is difficult due to the subjective nature of tinnitus. Some of the existing pitch matching methods present a challenge for both patients and clinicians, and require multiple adjustments of frequency and loudness, which becomes increasingly difficult in case of coexisting hearing loss. In this paper, we present the comparison in terms of reliability between two self-guided pitch matching methods: the method of adjustment (MOA) and the multiple-choice method (MCM). Methods 20 participants with chronic tinnitus and hearing loss underwent the two assessments in two different sessions, 1 week apart. Measures of intraclass correlation (ICC) and difference in octaves (OD) within-method and within-session were obtained. Results Both methods presented good reliability, and the obtained values of ICC and OD suggested that both methods might measure a different aspect of tinnitus. Discussion Our results suggest that a multiple-choice method (MCM) for tinnitus pitch matching is as reliable in a clinical population as more conventional methods.